2020
DOI: 10.3390/s20030600
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Emissive Metallo-Supramolecular Assemblies of Quinoline-Based Acyl Hydrazone

Abstract: Development of fluorescence-based sensory materials for metal elements is currently in the mainstream of research due to the simplicity and usability of fluorescence as a method of detection. Herein, we report a novel “bis”-quinoline-based acyl hydrazone—named bQH that could be synthesized by a facile, low-cost method through simple condensation of hydrazide with an aldehyde. This acyl hydrazone showed emissive properties through Zn selective binding, especially in its solid-state, as shown by experiments such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In our previous work, it was found that the emission of quinoline-based acylhydrazone was enhanced upon binding to Zn 2+ by the planarization of the molecular structure. It was interesting that the Zn 2+ complex of the bis-acylhydrazone and similar compounds showed the enhanced emission in the solid state, which led us to investigate their origin of solid-state emission.…”
Section: Resultsmentioning
confidence: 97%
“…In our previous work, it was found that the emission of quinoline-based acylhydrazone was enhanced upon binding to Zn 2+ by the planarization of the molecular structure. It was interesting that the Zn 2+ complex of the bis-acylhydrazone and similar compounds showed the enhanced emission in the solid state, which led us to investigate their origin of solid-state emission.…”
Section: Resultsmentioning
confidence: 97%
“…They undergo easy dehydration to 1,3,4-oxadiazoles that present a variety of biological activities [33,34]. Hydrazide-hydrazones provide interesting properties in the field of supramolecular architecture [35][36][37][38][39], organic synthesis [33,40], chemo-and physical imaging [41][42][43][44], coordination [45][46][47][48][49], and in inorganic chemistry [50][51][52][53]. The numerous biologically active hydrazide-hydrazones are particularly worth paying attention to [54].…”
Section: Introductionmentioning
confidence: 99%
“…But among them fluorimetric measurement is of abiding interest due to its high selectivity and sensitivity . A good number of hydrazone compounds have been reported very recently as a sensor for the detection of aluminum ion and zinc ion or dual sensing for both the metal ions utilizing fluorescence spectroscopy in solution as well as in solid state . In connection with this, the spectroscopic identification and detection of zinc and aluminium using a hydrazone based ligand is in great demand now to find an easier, cheap, less time consuming synthetic route and corresponding uncomplicated precise detection of target metal ions.…”
Section: Introductionmentioning
confidence: 99%